1999
DOI: 10.1016/s0091-6749(99)70496-3
|View full text |Cite
|
Sign up to set email alerts
|

Sputum analysis, bronchial hyperresponsiveness, and airway function in asthma: Results of a factor analysis

Abstract: Background: Recent studies have shown weak associations among FEV 1 , bronchial hyperresponsiveness (BHR), sputum eosinophils, and sputum eosinophil cationic protein (ECP), suggesting that they are nonoverlapping quantities. The statistical method of factor analysis enables reduction of many parameters that characterize the disease to a few independent factors, with each factor grouping associated parameters. Objective: The purpose of this study was to demonstrate, by using factor analysis, that reversible air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 31 publications
4
111
1
10
Order By: Relevance
“…Recently, CRIMI et al [34] and ROSI et al [35] were able to demonstrate that BHR is independent of the number of inflammatory cells in the airway lumen or mucosa. The present results, showing the independence among sputum cellular and biochemical profile, volume history and BHR are in line with the results of these studies [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CRIMI et al [34] and ROSI et al [35] were able to demonstrate that BHR is independent of the number of inflammatory cells in the airway lumen or mucosa. The present results, showing the independence among sputum cellular and biochemical profile, volume history and BHR are in line with the results of these studies [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Une analyse factorielle a toutefois révélé que l'inflammation des voies aériennes et l'hyperréactivité bronchique à la méthacholine donnent des informations différentes [88] . Une étude récente a objectivé un seuil de FE NO Intérêt pour la prédiction des exacerbations, du déclin de la fonction respiratoire, du contrôle et de la sévérité de l'asthme, de la réponse au traitement et de l'adaptation du traitement anti-inflammatoire…”
Section: Intérêt Pour Le Diagnostic De L'asthmeunclassified
“…In view of the disease heterogeneity, traditional disease markers, such as clinical symptoms and lung function parameters, appeared inadequate to differentiate across the various subsets or to monitor disease activity and the response to (targeted) therapy, since they appeared poorly correlated with the underlying airway inflammation [15]. In addition, several factor and cluster analyses revealed that symptoms and lung function, markers of airway inflammation and airway hyperresponsiveness provide complementary information on the severity and activity of asthma in both adults and children and can help to differentiate into different asthma phenotypes [16][17][18][19]. In this respect, the development of non-invasive airways sampling methods and detection techniques, allowing identification of several components of the airway inflammation including the determination of useful biomarkers, has greatly contributed to our current insight into the inflammatory cascades within several asthma subsets and the link to customized, targeted therapies [13,20,21].…”
Section: Pathophysiology Of Allergic Airways Diseasementioning
confidence: 99%